Apresentação oral nas aulas de língua espanhola: desempenho lingüístico, fatores afetivos e avaliação da atividade - Zeulli, Elizandra (2007)
This work aims at investigating the characteristics of oral presentations made in Spanish classes and verifying: how the students in the audience, the researcherteacher and the presenter act during these activities; the affective aspects revealed by the students and the evaluation they make of such activities; as well as observing the linguistic problems revealed at the oral presentations. The set of participants consists of five students taking the last year of a Language course in Portuguese and Spanish and their respective literatures, and the teacher of the group, who is also the researcher. The research took place in a private college in the State of São Paulo inland. The data were collected in Spanish language classes in 2005. The instruments for data collecting were: two questionnaires, guided oral interviews, audio recordings, assessment cards, conversation based on the assessment cards, and field notes. This study is based on theories of: oral presentation in several contexts (Goffman,1981, Ander-Egg & Aguilar ,1981, among others) and in the educacional context (Graham,1994, Underhill, 1987, among others); the communicative approach (Almeida Filho, 1993, Widdowson, 1991, Scott, 1981, Breen & Candlin,1980); communicative competence (Savignon, 1983, Canale & Swain, 1980, among others); Brazilians speaking Spanish (Ferreira, 1997, Kulikowski & González, 1999, Alcaraz, 2005, Almeida Filho, 1995); and finally, the concept of transference (Selinker, 1972, Lado, 1957, Kellerman,1978, Cruz , 2004). The results reveal the students consciousness raising of: their linguistic problems, their roles as students and their responsabilities as future teachers, the procedures which can reduce affective factors and the importance of oral presentations as a pedagogical activity. Finally some researcher-teacher s reflections on this study and its contributions to the area of foreign language teaching and learning are presented